2013
DOI: 10.1161/strokeaha.113.002471
|View full text |Cite
|
Sign up to set email alerts
|

Suprascapular Nerve Block for Shoulder Pain in the First Year After Stroke

Abstract: Background and Purpose-Shoulder pain is a common complication after stroke that can impede participation in rehabilitation and has been associated with poorer outcomes. Evidence-based treatments for hemiplegic shoulder pain are limited. Suprascapular nerve block (SSNB) is a safe and effective treatment of shoulder pain associated with arthritic shoulder conditions, but its usefulness in a stroke population is unclear. Methods-We undertook a randomized controlled trial assessing the effectiveness of SSNB in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 39 publications
1
36
1
3
Order By: Relevance
“…In our study, it is clearly seen that suprascapular nerve block is effective for pain management in case of hemiplegic shoulder pain. The results were found similar and comparable with Adey-Wakeling et al 22 The pain reduction was seen with more than >20 mm reduction in VAS scale at 1 st week with suprascapular nerve block. Also the VAS scale improved significantly at each follow up with comparable results.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, it is clearly seen that suprascapular nerve block is effective for pain management in case of hemiplegic shoulder pain. The results were found similar and comparable with Adey-Wakeling et al 22 The pain reduction was seen with more than >20 mm reduction in VAS scale at 1 st week with suprascapular nerve block. Also the VAS scale improved significantly at each follow up with comparable results.…”
Section: Discussionsupporting
confidence: 87%
“…A recent randomized, clinical trial showed that suprascapular nerve blocks were superior to placebo injections in reducing hemiplegic shoulder pain for up to 12 weeks after treatment. 145,146 In another small, comparison study of patients with nonneuropathic hemiplegic shoulder pain, suprascapular nerve blocks were as effective as glenohumeral triamcinolone injections. 147 Surgical tenotomy of the pectoralis major, lattisimus dorsi, teres major, and subscapularis muscles may reduce pain in patients with severe hemiplegia and restrictions in shoulder range of motion.…”
Section: Assessment Prevention and Treatment Of Hemiplegic Shouldermentioning
confidence: 99%
“…In a randomized placebo-controlled trial by AdeyWakeling et al, [23] blinded application of SSNB has been reported to be a safe and effective treatment for patients with HSP.…”
Section: Discussionmentioning
confidence: 99%